Anticancer activity of Alpinia purpurata (Vieill) K. Schum. against MNU and testosterone induced prostate cancer in male Wistar albino rats - Anusooriya Palanirajan; Poornima Kannappan; Gopalakrishnan Velliyur Kanniappan (Elsevier, 2022)
Background: Numerous Chinese herbal extracts have been proved to inhibit the development of prostate cancer. Zingiberaceae family is one type of plant used as an ingredient in traditional Chinese medicine (TCM). The genus Alpinia species of the Zingiberaceae family are well-known traditional herbal medicine for anti-inflammatory, antioxidant, antimicrobial, anti-dermatophytic, anti-nociceptive, hepatoprotective, immune stimulatory and anticancer activities. In vivo anticancer activity of Alpinia purpurata were studied in MNU and testosterone induced prostate cancer rats. Methods: The induction of prostate cancer by using Wistar strain rats. The animals were divided into five groups. Group 1- Control, normal healthy rats Group 2- Rats were induced prostate cancer by daily intraperitoneal injection of testosterone (T) (100 mg/kg bw) in 0.3 ml propylene glycol for 3 days. One day after the testosterone injection, all the rats received intravenous injection of N-methyl N-nitrosourea (MNU) (50 mg/kg bw) (dissolved in saline at 10 mg/ml), through the tail vein for a period of one week. One week after MNU administration, rats received daily intraperitoneal injection of 2 mg/kg bw testosterone for 60 days. Group 3 - Rats were treated as group 2 along with Finasteride (25 mg/kg bw) supplemented throughout the entire experimental period of 2 months. Group 4 - Rats were treated as group 2 and simultaneously treated with daily dose of 200 mg/kg bw of the crude leaf ethyl acetate extract of Alpinia purpurata through oral gavage for 2 months. Group 5 - Rats were received daily dose of 200 mg/kg bw of crude, leaf ethyl acetate extract of Alpinia purpurata through oral gavage for 2 months. After the experimental period of 4 months, the animals were sacrificed by cervical dislocation under mild chloroform anesthesia. All biochemical parameters and histopathological studies were carried out. Results: The biochemical parameters such as total protein, enzymatic and non-enzymatic antioxidants and membrane bound enzymes were decreased whereas LPO, tumor markers, nucleic acid constituents were increased in prostate and seminal vesicle tissues of cancer induced group. The hematological, lipid parameters were altered and prostate markers, renal markers and liver markers were increased in serum. Those levels were brought back to near normal upon treatment with ethyl acetate leaf extract of Alpinia purpurata and standard drug finasteride. No significant changes were observed on treatment with plant extract alone group which indicated that there is no toxic substance present in Alpinia purpurata which was confirmed by the histopathological analysis of organs liver, kidney, prostate gland and seminal vesicle. Conclusion: On the basis of our findings, it is concluded that Alpinia purpurata might be used as an anticancer agent for the management of carcinoma in future.